2019
DOI: 10.1590/2237-6089-2018-0089
|View full text |Cite
|
Sign up to set email alerts
|

Female crack cocaine users under treatment at therapeutic communities in southern Brazil: characteristics, pattern of consumption, and psychiatric comorbidities

Abstract: Objective To explore and describe sociodemographic characteristics, crack consumption patterns, and psychiatric comorbidities of female crack users receiving treatment at therapeutic communities. Methods This was a cross-sectional, descriptive, quantitative study. Forty-six women who abstained from crack use were assessed using a sociodemographic questionnaire, the Mini-Mental State Examination (MMSE), the Structured Clinical Interview for DSM-IV Axis I Disorders (SCID-I), and a profile of crack use questio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 26 publications
(26 reference statements)
1
0
0
Order By: Relevance
“…Hess and collaborators (2019) carried out a study to observe the social characteristics correlated with the number and length of stay of women in prolonged inpatient treatment. No difference was seen in respect of the factors of age, race, education, and criminal history (Hess;De Almeida, 2019). Our data agree with these findings, as we did not observe a relationship between these sociodemographic factors and treatment dropout.…”
Section: Discussionsupporting
confidence: 90%
“…Hess and collaborators (2019) carried out a study to observe the social characteristics correlated with the number and length of stay of women in prolonged inpatient treatment. No difference was seen in respect of the factors of age, race, education, and criminal history (Hess;De Almeida, 2019). Our data agree with these findings, as we did not observe a relationship between these sociodemographic factors and treatment dropout.…”
Section: Discussionsupporting
confidence: 90%
“…On the other hand, CUD patients usually display a high prevalence of psychiatric comorbidities associated with other substance use disorders and other mental disorders. Our results indicate that mood, anxiety and personality disorders as well as alcohol and cannabis use disorders were the most frequent among abstinent CUD patients, as many other studies have reported [9,13,[56][57][58][59]. Regarding its association with sex-based differences, in our study, women began using cocaine later and exhibited higher rates of anxiety and eating disorders, whereas men showed more cannabis use disorders.…”
Section: Discussionsupporting
confidence: 73%
“…In the same line, previous studies have suggested that women suffer more with generalized anxiety disorder, post-traumatic stress disorder, anorexia and bulimia, which may be considered risk factors for the development of CUD. In contrast, men are more likely to develop other substance use disorders-except for sedatives [6,16,59]. Thus, alcohol use has been biologically demonstrated to increase the risk of compulsive cocaine consumption [60].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation